Women, Confl ict and Peace in the Grassfi elds of Cameroon - Jean Gormo, Mark Bolak Funteh (Africana Studia, 2020)
Many schools of thought hold that the presence of the Grassfi elds women was felt in the domain of subsistence farming, long and short-distance trade, manufacturing local liquor and clothes, informal education of the girl child, and above all, child bearing. Their political duties, revolved around palace administration, and when they acted out of this political responsibility, they remained mere victims of confl ict. But history continually records accounts of these women getting involved in far complicated political and other societal issues than just these. Their involvement in confl ict as combatants, made manifest in their actions as instigators, service providers and political activists, and confl ict resolutionists, has not been able to hide. In the face of these situations, the courageous image of the women grew increasingly perceptible while that of their men remained so indiscernible. This of course, brings these schools’ opinion about the status of the women to book. Given this situation, efforts in the Grassfi elds are being made to seek new approaches to evaluate the role of the woman in the effective evolution of the region, especially in the domains of conflict and peace. This quest has led to a school which advocates the active participation of women in politics, especially in the domain of confl ict and confl ict resolution. This essay falls in line with this approach as it examines the mixed character of the Grassfi elds women during conflict situations, particularly as combatants and peace promoters. Keywords: Cameroun; history of gender; confl ict resolution and shepherding.